The Role of Communication Self-Efficacy in Innovative Work Behavior among Manufacturing Employees in Medan City - Farida Hanum Siregar; Ira Kesuma Dewi; Endang Haryati; Andy Chandra; Azhar Aziz (Golden Ratio of Social Science and Education, 2026)
Innovative Work Behavior (IWB) has become an essential factor enabling organizations to adapt to environmental changes and maintain long-term competitiveness. One psychological factor that may promote innovative behavior is Communication Self-Efficacy, which refers to employees' confidence in their ability to communicate effectively in the workplace. This study aimed to examine the role of Communication Self-Efficacy in predicting Innovative Work Behavior among manufacturing employees in Medan, Indonesia. A quantitative correlational design was employed involving 217 employees selected through purposive sampling. Data were collected using the Communication Self-Efficacy Scale and the Innovative Work Behavior Scale and were analyzed using Pearson correlation and simple linear regression with IBM SPSS Statistics 27. The findings revealed a positive and significant relationship between Communication Self-Efficacy and Innovative Work Behavior (r = .61, p < .001). Regression analysis further demonstrated that Communication Self-Efficacy significantly predicted Innovative Work Behavior (β = .61, t = 11.31, p < .001), explaining 37.3% of the variance (R² = .373). These findings indicate that employees with greater confidence in their communication abilities are more likely to generate, promote, and implement innovative ideas in the workplace. Theoretically, this study extends the application of Social Cognitive Theory by highlighting communication self-efficacy as an important psychological antecedent of Innovative Work Behavior. Practically, the findings suggest that organizations should strengthen employees' communication self-efficacy through communication skills training, coaching, and supportive communication climates to foster sustainable innovation and organizational performance.